2018
DOI: 10.2196/jmir.9036
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors of Health Professionals’ Intention to Use a Decision Aid for Down Syndrome Screening: Cross-Sectional Quantitative Study

Abstract: BackgroundDecisions about prenatal screening for Down syndrome are difficult for women, as they entail risk, potential loss, and regret. Shared decision making increases women’s knowledge of their choices and better aligns decisions with their values. Patient decision aids foster shared decision making but are rarely used in this context.ObjectiveOne of the most promising strategies for implementing shared decision making is distribution of decision aids by health professionals. We aimed to identify factors in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The intention to use a DA was chosen as an outcome because it facilitates the implementation of SDM in clinical practice [ 27 ]. Intentions have already been documented as a strong measure of predicting a behavior [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intention to use a DA was chosen as an outcome because it facilitates the implementation of SDM in clinical practice [ 27 ]. Intentions have already been documented as a strong measure of predicting a behavior [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was determined in reference to a previous study in the field [ 27 ] that examined the intention to use a DA for Down syndrome screening among other prenatal care providers, namely gynecologists, general practitioners, and midwives. The mean intention score for midwives in this study was 5.78 (SD 0.84).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 14 studies were available from which to select relevant data sets. 1427 Almost all the studies were conducted within or in collaboration with the Université Laval Primary Care Practice-Based Research Network across provinces in Canada. This network comprises 12 family practice teaching units affiliated with Université Laval and collaborates with other research networks nationally and internationally.…”
Section: Methodsmentioning
confidence: 99%
“…Articles were eligible if they related to decision-making or the implementation of SDM or decision aids in decisions about Down syndrome prenatal screening. The articles described results from: (a) a systematic review of the decisional needs of participants in Down syndrome prenatal testing [29], (b) a crosssectional study examining the levels of SDM and decisional conflict during routine consultations about Down syndrome prenatal testing [13,30,31], (c) an environmental scan of decision aids for Down syndrome prenatal screening [32], (d) two mixed-methods studies examining pregnant women's [33][34][35] and health professionals' [36,37] intentions to use a decision aid for Down syndrome prenatal screening, and (e) a theorybased qualitative study examining women's perceptions of strategies to enhance the use of a decision aid for Down syndrome prenatal screening [38].…”
Section: Data Collectionmentioning
confidence: 99%
“…Using the Theoretical Domains Framework as a guide, our team found that women's intentions to use decision aids were influenced by a range of factors, including their attitudes and beliefs, their knowledge and skill levels, the nature of the decision aid itself, and the context in which they encountered it [34,35]. Health professionals also generally showed strong intentions to use decision aids but this varied by type of professional, with midwives having the highest intentions and obstetrician/gynecologists having the lowest [37]. Professionals' intentions to use decision aids were similarly influenced by many factors, including their attitudes and beliefs about the decision aidand their own professional identity, the compatibility and availability of the decision aid within their practice, and the use of decision aids by their peers [36,37].…”
Section: Knowledge Creation Knowledge Inquirymentioning
confidence: 99%